Development and characterization of an automated portable wound irrigation device for diabetic ulcers - Nadhif, Muhammad Hanif; Assyarify, Hanif; Irsyad, Muhammad; Yunir, Em; Edi Tarigan, Tri Juli; Sarumpaet, Angela; Iswati, Eni (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Patients with diabetes mellitus may experience peripheral neuropathy and extremity system impairment, which may lead to ulceration if the treatments are delayed. Diabetic ulcers, unfortunately, are chronic, which require proper treatments, including debridement and bacterial removal using an irrigation device. To date, commercial irrigation devices included pulsed-lavage, bulb syringe, and gravity bags. Unfortunately, the devices have limitations in terms of portability, measurability, controllability, and disposability. To tackle the limitations, this study aims to design, fabricate, and characterize an automated portable wound irrigation device (Apdice), which is controllable non-disposable, and portable. The device was designed and fabricated using a lightweight construction, a rechargeable battery, and non-disposable materials to support the portability and non-disposable means. Meanwhile, the proportional-derivative-integral controller with its peripheral components were featured to enable controllability. Furthermore, the device was also tested regarding the contamination using a particle counter, and appeared to be contamination free. In short, Apdice showed a robust technological performance. However, it is also worth the try to test the contamination test against biological agents to guarantee the biocompatibility of the device.